Introduction to Project Management - The Case of GIZ Projects - Lacroix, Eric J. (Khulna University, 2015)
In this course, we will try to understand the complexity and the struc ture of the management of a development project implemented by the GIZ for the German Development cooperation. We will first define the fram e of management and project to enter in the map of two logics. Then, w e will overfly the 5 success factors of Capacity WORKS, with concrete examples in annexe. It will bring us to the monitoring, the standard p rocesses in GIZ cooperation projects, the basic tools for project impl ementation and the evaluation. The team building will allow us to ente r in a specific aspect of project management.